Ground vibration testing of a high aspect ratio wing with revolving clamp - Dessena, Gabriele; Ignatyev, Dmitry; Whidborne, James F.; Pontillo, Alessandro; Zanotti Fragonara, Luca (International Council of the Aeronautical Sciences (ICAS), 2022)
The advancements in the aeronautical industry and research on materials and manufacturing methods in the last 70 years have been shifting the paradigm of wing design to high aspect ratio flexible wings. These wings can show a varying behaviour in different operating conditions, as per the nature of their geometry and materials. This work proposes a case study of a high aspect ratio flexible wing in order to study the effect of operating conditions on its structural properties. To test different operating conditions on the ground, a revolving clamp is designed to attach the specimen to a clamp-on shaker. A clear relationship between the wing’s modal properties, and so structural properties, and the angle the clamp sets is found.
© The Author
Keywords: Experimental Modal Analysis; Ground Vibration Testing; High Aspect Ratio; Structural Dynamics; Flexible Wing